The influence of creative accounting on the professional ethics of the public accountant - Hernández-Gil, Cristian; Losada-Rodríguez, Nelson Andrés; Orozco-Calderón, Daniela (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The public accounting as a professional career, born from the need to train people, in a technical, professional and ethical way to specialize and handle the management of the finances of a natural or legal person, for a subsequent presentation of financial reports with reliable figures, in order to perfect the development of the decision-making process from the management of any organization. Based on this, the objective of this research is to analyze the ethics of the professional, its importance and how the absence of it leads to the presentation of creative accounting. To this end, a descriptive and documentary review type research was carried out, in which 51 bibliographical references were analyzed. It is concluded that creative accounting is a scourge that affects the organizational and professional ethics of those who allow to commit fraudulent acts for the simple reason of accommodating figures and showing a reality that does not correspond to what is truly executed.